Microbiota Succession and Chemical Composition Involved in the Radish Fermentation Process in Different Containers - Liu, Lei; She, Xiao; Chen, Xing; Qian, Yang; Tao, Yufei; Li, Yalin; Guo, Shuyu; Xiang, Wenliang; Liu, Guorong; Rao, Yu (Frontiers in Microbiology, 2020)
Traditional Chinese fermented vegetables are a type of brine-salted fermented vegetable product. During the spontaneous fermentation, various compounds are produced, degraded, and converted, influencing the quality of the fermented pickle. To ascertain the effect of different containers on the fermentation process of the pickles, this study investigated the bacterial diversity and the chemical composition characteristics of the pickle (radish) fermented in commonly used containers including glass jars (GL), porcelain jars (PO), and plastic jars (PL). The correlation between chemical compounds and microbial community was further analyzed. The changes in pH values suggested that PL may facilitate the quickest fermentation of the pickles, while the process in PO progressed at the lowest rate. The PL brine samples contained higher levels of lactic acid and threonine, while more abundant volatile chemical compounds were evident in PO. The container materials had no significant influence on the microbial structure, wherein Lactobacillus was the absolute dominant genus in all containers. But container material did have an effect on the abundance of specific genus, such as Lactococcus and Pediococcus. The correlation between these major genera was also analyzed and gene function prediction indicated that the top three pathways were: carbohydrate metabolism, amino acid metabolism, and energy metabolism. Lactobacillus negatively correlated with methionine, tyrosine, lysine, and arginine, but positively correlated with ammonia, and lactic acid and acetic acid both just correlated with Pediococcus. This study provides new insights into the microbiota succession and chemical compounds involved in the vegetable fermentation.